PENGEMBANGAN PERANGKAT PEMBELAJARAN KONTEKSTUAL PADA MATERI PECAHAN - Robia Astuti (Universitas Muhammadiyah Pringsewu, 2016)
The purpose of this study is to develop the set of contextual teaching learning model which increase the quality of math learning. The population of this research are the students on VII class of SMPIT-Al-Munir Sukoharjo III in the academic year 2014-2015 that consist of 28 students. In this research, all of the member of population be the sample because the population is less than 30. In developing the set of learning, the researcher uses 4-D model (Define, Design, Develop, and Disseminate). The data collecting technique used was test, questionnaire, and observation (observation the application of lesson plan and observe the students' activity). The research finding namely set of learning by using contextual learning model that consist of lesson plan, students' worksheet and the test of the learning achievement that is measured from the ability in activate the students and teacher whose all of them included in good category. Keywords: contextual teaching learning model, 4-D model